Religious identity and «Kyrgyz ZHarany» in search of dialogue (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Religious identity in Kyrgyzstan, being part of the general civic identity, reaches a new level and acquires a political overtones. State-confessional relations require a new format of approach on the part of the state. Dialogue and an integrated strategic approach are needed to form mutually beneficial cooperation and partnership in building the civic identity of “Kyrgyz Zharany”.
Keywords: religion; religious identity; freedom of religion; confession; faith; family; traditions and customs; state; state-confessional relations; religiously motivated extremism; general civic identity “Kyrgyz Zharany”